2011
DOI: 10.1111/j.1834-7819.2011.01363.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved periodontal health and cardiovascular risk

Abstract: Background: Previous studies have demonstrated variable effects on systemic inflammatory and immune responses following improved periodontal health. This study examined changes in serum levels of the inflammatory mediators IL-1b, IL-6, TNF-a and sICAM-1, and antibodies to Porphyromonas gingivalis, human heat shock protein (hHSP) 60 and P. gingivalis GroEL following improvement in periodontal health in high cardiovascular (CV) risk and low CV-risk patients. Methods: Patients retrospectively selected from a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…No evidence of a similar effect of periodontal therapy on sICAM-1 and sVCAM-1 was found (Lalla et al 2007, Pischon et al 2007, Marcaccini et al 2009a. We found only one trial reporting a reduction of sICAM-1 after periodontal therapy in patients with low CVD risk (Rose-Hill et al 2011).…”
Section: Circulating Cell Adhesion Moleculesmentioning
confidence: 74%
“…No evidence of a similar effect of periodontal therapy on sICAM-1 and sVCAM-1 was found (Lalla et al 2007, Pischon et al 2007, Marcaccini et al 2009a. We found only one trial reporting a reduction of sICAM-1 after periodontal therapy in patients with low CVD risk (Rose-Hill et al 2011).…”
Section: Circulating Cell Adhesion Moleculesmentioning
confidence: 74%
“…We found only one trial reporting a reduction of sICAM‐1 after periodontal therapy in patients with low CVD risk (Rose‐Hill et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the effect of periodontal treatment on these biomarkers is variable and inconclusive. For example, one study (118) showed a decrease in the serum levels of soluble intercellular adhesion molecule‐1 with improvement in periodontal health, while another (110) showed no change following periodontal therapy. These results again emphasize the need for more studies, with larger sample sizes, over a longer term.…”
Section: Cardiovascular Diseasementioning
confidence: 99%